THE INFLUENCE OF FINANCIAL RATIO ON PROFIT GROWTH IN MINING COMPANIES IN INDONESIA - Sri Handini; R. Agus Baktiono; Bambang Raditya Purnomo (STIE Mahardhika, 2023)
The purpose of this research is to test empirically the impact of the Dividend Payout Ratio (DPR), Net Profit Margin (NPM), and Return on Assets (ROA) on company profit growth. The samples used in this study were 17 mining sector companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2019 period. Samples were taken using a census (saturated sample), namely by using the entire population as the sample. The data used are secondary data obtained from the IDX and the Annual Reports of each sample company. The data analysis technique used is multiple linear regression analysis technique. The results showed that partially, the Dividend Payout Ratio (DPR) had a positive but not significant effect on profit growth, while Net Profit Margin (NPM) and Return On Assets (ROA) had a positive and significant effect on profit growth. Simultaneously, Return On Assets (ROA), Net Profit Margin (NPM), and Dividend Payout Ratio (DPR) have a positive and significant effect on profit growth.